A Dissertation Report On PP On Net-People Process Anywhere Anytime - SHASHIKALA G (2010)
INTERNAL GUIDE : Avayambal K . EXTERNAL GUIDE : Murali Kailasam USN No : 1MJ09SCS14 CARRIED OUT AT : Illume-Tech Solutions And Services Bangalore- ACC NO : PC102
Keywords: Process Anywhere Anytime